MODEL PEMBERDAYAAN PETERNAK SAPI MELALUI DISEMINASI, NUTRIFIKASI, DETEKSI ESTRUS DAN INSEMINASI BUATAN PADA KELOMPOK TANI FAJAR II - Muhammad Mirandy Pratama Sirat; Ratna rmawati Ermawati; Lusia Komala Widiastuti; Siswanto Siswanto; Liman Liman; Ferry Pebriyansyah (Universitas Nusa Cendana, 2026)
The Fajar II Farmers Group is a livestock-oriented farmers’ association engaged in the management of ruminant animals. The program was implemented among 18 cattle farmers who are members of the group during June–August 2025. The implementation methods were survey and coordination; 2) Dissemination through extension activities and participatory discussions; 3) Nutrification via training on the formulation and proximate analysis of complete feed; 4) Training on estrus detection and recording of animal health and reproductive performance; and 5) Monitoring and evaluation of the overall activities. The evaluation results demonstrated that: 1) Farmers’ knowledge regarding cattle management, reproduction, and health increased by 30.52%, shifting from medium to high categories; 2) Farmers successfully formulated PUNILA complete feed during nutrification training with an average crude protein content of 16.90 ± 1.54%; and 3) Artificial insemination was performed on four cows identified through independent estrus detection by farmers. The conclusions of this community service program demonstrate a substantial improvement in farmers’ knowledge and technical capacities in cattle husbandry, nutrification, and reproductive management. These advancements were supported by the dissemination of knowledge and hands-on training in the formulation of PUNILA complete feed based on locally available feed resources, as well as estrus detection for artificial insemination. Collectively, these interventions contribute to efforts to increase cattle population, thereby supporting the Government of the Republic of Indonesia’s target of achieving national beef self-sufficiency.